The impact of the juvenile vandalism in the public urban space. The case of Parsabad’s city in Iran. - Karimian Bostani, Maryam; Sadeghi, Mohsen; Aghai, Aliakbar (Espacio Abierto, 2018)
Vandalism is a social phenomenon that results in the destruction of public facilities. Vandalism has a variety of adverse impacts on the urban public space. The purpose of this article is to study vandalism and its impact on the urban public realm in Parsabad (a highly populated city in Ardebil province adjacent to the Azerbaijan Republic). This study is a quantitative research carried out based on survey techniques and the data collection tool was a prefabricated questionnaire. The statistical research population includes all 12 to 20 years-old teenagers living in the city of Parsabad in the year 2017 with a size of 33922 persons. The sample size was379 based on standard Morgan table. The research findings based on SPSS software and t-test show that the most important factors in the occurrence of vandalism in the city of Parsabad are revenge against injustice, to prove oneself and show off, amusement and entertainment, fight against the existing socialorder, hanging around with vandals, and claiming power and prestige in the gang. Also, according to Friedman’s test results,revenge against injustice with 38%, to prove oneself and show off with 18%, amusement and entertainment with 14%, fight against the existing social order with 12%, hanging around with vandals with 10%, and claiming power and prestige in the gang with 8% rank first to sixth in the order of factors. Also, graffiti writing, tearing down, arson, and breaking the public property are some impacts of vandalismon the public propertiesand spaces in the city of Parsabad.